Online KidClot education for patients and families initiating warfarin therapy: The eKITE study. Issue 215 (July 2022) - Bauman, M.E.; Hellinger, A.; Pluym, C. Vander; Bhat, R.; Simpson, E.; Mehegan, M.; Knox, P.; Massicotte, M.P.
Abstract: Anticoagulation with Vitamin K antagonists (VKA) has always posed challenges in terms of monitoring requirements. These challenges were further exacerbated in the setting of the COVID-19 pandemic, with limited access to and/or avoidance of laboratory testing. The importance of utilizing point of care (POC) health technology for individualized patient management is salient. The foundation of effective home INR monitoring is establishing patient knowledge about their therapy and INR testing proficiency. The eKITE series was developed to support patients in establishing foundational knowledge required for VKA (warfarin) management and INR monitoring. The primary objectives were to evaluate eKITE, a patient-oriented innovative online education program for warfarin therapy, participant learning stress, and patient preference for online learning. This multi-center prospective study provided patients access to warfarin online education. Participants were required to complete written quizzes assessing warfarin knowledge of key concepts proficiency and identifying knowledge deficits. Patient preference, evaluating calm (lack of anxiety) while learning, and an INR on a home meter was completed. Participants performed INR tests at home and reported INRs by telephone. The analysis included 144 children and caregivers enrolled at five US and CDN sites. Most indications for anticoagulation were cardiac (congenital or acquired heart disease) with varied INR target ranges. Mean knowledge scores for warfarin and INR self-testing modules were 97%, with low anxiety with TTR of 84%. Patient preferred online learning. eKITE is an effective teaching modality for warfarin/home INR monitoring with safe INR testing and warfarin management that is appropriate for pediatrics and adults alike. Prologue: The whir in the hallways is deafening. Lights bright, alarms are ringing in a chorus of unsynchronized beeps and screeches. It has been more than a week since I have slept. Snuggled beside me is my precious child, whining and equally irritated with the asynchronous symphony, further compounded by anxiety, procedures, and pain. The sun has broken. The staff smiles are welcoming and incessant, as one after one, they approach hurried, urgent, assiduous, their need to coach me for our upcoming departure to the warmth of home. Each provides essential information that I will require to keep my child, my treasure, safe and healthy. Yet, my eyes are heavy, blurred, and my brain foggy, trapped in a dark heavy cloud. How am I to follow? Comprehend? and retain anything? As they instruct, my precious child yearns for loving arms, compassion and love, whining, crying in disquiet. Overwhelmed does not adequately describe my ineffable exhaustion. Amidst this, how am I to learn about warfarin? Such a challenging medication, with so much to know. Concentrate, I tell myself, focus; now is my only opportunity to learn. I must be alert. It seems to be nonsensical. Highlights: Warfarin education is pivotal to safe and effective warfarin management. eKITE online warfarin teaching is effective and preferred by families. INR time in the therapeutic range demonstrates patient learning. Home INR monitoring facilitates social distancing for providers and patients.